Antimicrobial Activity of Lactic Acid Bacteria Thermophilic Isolated from Hot Spring Rimbo Panti of West Sumatera for Food Biopreservatives - yah, Nurjama; Marlida, Yetti; Arnim; Yuherman (Pakistan Journal of Nutrition, 2014)
Rimbo Panti hot springs located bordering the province of West Sumatra and North Sumatra, precisely in the District of East Pasaman Pasaman regency of West Sumatra Province approximately 200km from the city of Padang. Hot water samples obtained from 5 pools which have a normal temperature of 50-95°C. The aim of this research was to isolate and identify Lactic Acid Bacteria (LAB) thermophilic activity from hot spring with pathogen bacteria (Escherichia coli O157: H7, Salmonella thypmurium and Listeria monocytogenes) followed identified by PCR. The bacteria isolated were growth on medium thermus cair and then deMan Rogosa and Sharpe (MRS) Agar supplement with CaCO3 1% and then performed purification by plate out on deMan Rogosa and Sharpe (MRS) Agar. It was found 23 isolates of LAB showed with clear zone around the culture and 5 isolates (N2, N4, N6, N9 and N12) has been antimicrobial activity against the growth of pathogenic bacteria. The results showed that isolates N6 had the highest antimicrobial activity against all bacteria test, with a range of inhibition zone 18-30 mm, gram positive, spore former coccus, non motility and catalase negative. LAB isolates that have the widest diameter of the clear zone continued to test the minimum inhibitory concentration (MIC). MIC values of isolates N6 supernatant against pathogenic bacteria Escherichia coli O157: H7 by 60 and 80% of the bacterial pathogen Salmonella thypmurium and 50% of the bacterial pathogen Listeria monocytogenes. Based on morphological examination and PCR analysis, the isolate N6 was primarily identified as Pediococcus pentosaceus strain A24 bacteria.